Morphological variation and affinities of the poorly known snake Atractus caxiuana (Serpentes: Dipsadidae) - Passos, Paulo; Ramos, Luciana O.; Pinna, Pedro H.; Prudente, Ana L.c. (Zootaxa, 2013)
Atractus caxiuana was recently described based on three specimens (two males and one female) from the Floresta Nacional de Caxiuanã, municipality of Melgaço, state of Pará, in the eastern portion of the Brazilian Amazon. Apart from the type series, no additional samples are known for the species. In this study, we report new specimens of A. caxiuana, providing new morphological data (meristic, morphometric, pholidosis, colour pattern, and hemipenis) and localities. We relate the variability displayed by the characters analyzed to sexual dimorphism, geographic variation, and ontogeny. Additionally, we provide detailed comparisons with A. collaris and putative sister species, and propose a new species group to accommodate this distinct and possible monophyletic assemblage.